FREQUENCY OF DIASTOLIC DYSFUNCTION IN ASYMPTOMATIC, NORMOTENSIVE TYPE-2 DIABETIC PATIENTS - Randhawa, Fawad Ahmad; Hussnain, Malik Tayyab; Nazir, Shaista; Masud, Faisal (Journal of Ayub Medical College Abbottabad, 2014)
Background: Diabetes mellitus affects heart in multiple ways and can affect virtually any part of heart specifically cardiac myocardium. Hence this involvement can severely affect the cardiac contractility resulting in severely debilitating symptoms of cardiac failure and hampering life. Early diagnosis therefore is of paramount importance as it can enable early diagnoses and treatment to counter the irreversible damage to the cardiac contractility dysfunction. The objective of this study was to determine the frequency of diastolic dysfunction in asymptomatic normotensive type-2 diabetics. Methods: In this descriptive case series, 150 consecutive patients with type-2 diabetes mellitus having normal blood pressure and normal resting electrocardiogram and without any symptoms of heart failure were selected from diabetes management center and Doppler echocardiography was performed. Pulmonary venous flow recordings were also obtained from the four-chamber view directed at the right upper pulmonary vein. Presence or absence of diastolic dysfunction will be documented in each case. Valsalva maneuver was used to unmask pseudo-normal patterns of ventricular filling. Results: Of the total, 72(48%) of patients had diastolic dysfunction. Conclusion: Type-2 diabetes mellitus is associated with diastolic dysfunction in the absence of other causes of diastolic dysfunction. Keywords: Diabetes Mellitus, Type-2, Diastolic dysfunction, Normotensive